Perception of DBS's students towards short messaging service (SMS) / Intan Nazella Mohd Shah ... [et al.] - Mohd Shah, Intan Nazella; Saleh, Noor Salinah; Jikus, Norslyvien Eva; Haris, Nurfaradila (2007)
Generally, according to Puneet Gupta in www.wirelessdevnet.com, SMS is a mechanism of delivery of short messages over the mobile networks. It is a store and forward way of transmitting messages to and from mobiles. The message (text only) from the sending mobile is stored in a central short message center (SMS) which then forwards it to the destination mobile. This means that in the case that the recipient is not available; the short message is stored and can be sent later. An interesting feature of SMS is return receipts. This means that the sender, if wishes, can get a small message notifying if the short message was delivered to the intended recipient. Since SMS used signaling channel as opposed to dedicated channels, these messages can be sent or received simultaneously with the voice, data, and fax service over a Global System for Mobile (GSM) network. SMS supports national and international roaming. This means that you can send short messages to any other GSM mobile user around the world. With the PCS networks based on all the three technologies, GSM, Code Division Multiple Access (CDMA) and Time Division Multiple Access (TDMA) supporting SMS, SMS is more or less a universal mobile data service, (http://www.gsmworld.com/).